PERSPEKTIF ISLAM TENTANG PLURALISME BERAGAMA: ANALISIS TAFSIR MAUDHUI - Muhammad Furqan; Muhammad Ikhsan Burhanuddin; Taqiy Jundi Rabbani (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This study explores the relationship between Islam and religious pluralism. It discusses different perspectives within Islam, advocating for recognition and tolerance of other religions, while addressing the challenges of maintaining Islamic identity. Emphasizing the importance of dialogue and mutual understanding, it aims to promote peace and harmony in our multicultural society.